Continuous In-Situ Polymerization of Complex-Based Films for High-Performance Electrochromic Devices - Yang-Bo Liu; Hao-Tian Deng; Li-Yi Zhang; Jing-Hao Wei; Feng-Rong Dai; Zhong-Ning Chen (Molecules)
Synthesis of uniform and stable electrochromic films on a conductive layer is one of the effective ways to construct high-performance electrochromic devices. The development of more convenient and feasible polymer film preparation technology is important and necessary. Herein, we demonstrated the development of a continuous in situ polymerization method to prepare electrochromic film on ITO glass through Schiff base condensation of a tetraamine Fe-based complex and organic di-/tri-aldehyde precursors. The electrochromic film was successfully coated on the surface of the ITO conductive layer and exhibited uniform morphology and excellent stability. Film P1 exhibited two reversible redox processes allowing two steps of electrochromic processes, including the oxidation of Fe(II) to Fe(III) at 1.05 V and oxidation of triphenylamine moieties to cation radicals at 1.4 V, which induced three stable color states from initial yellow to orange red and blue. The utilization of the so-formed polymer film for the fabrication of electrochromic devices gave rise to excellent electrochromic performance of fast response time of 0.4−1.2 s and high coloration efficiencies of 241.5−352.9 cm2/C at 1.9 V (at 535 nm) and 2.5 V (at 755 nm). The present work provides a new feasible strategy for constructing polymer films for high-performance electrochromic devices.